1996
DOI: 10.1111/j.1600-0560.1996.tb01429.x
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of the transepithelial elimination of the collagen bundles in acquired reactive perforating collagenosis

Abstract: Two cases of acquired reactive perforating collagenosis with poorly controlled diabetes mellitus were studied by histochemistry and by electron microscopy. In excoriated wound the necrotic mass on the bottom of the ulcer contained the collagen bundles which were continuous with the collagen bundles in the reticular layer. In the developing stage, the epidermis regenerated between the necrotic mass and the reticular dermis, and the collagen bundles in the reticular dermis were in continuity with those in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
2
15
0
7
Order By: Relevance
“…ARPC has been described in association with diabetes, chronic renal disease and malignancy and following various inflammatory cutaneous conditions [18, 19]. It corresponds to a transepidermal elimination of necrotic collagen during a peculiar pattern of epidermal regeneration [20]. Overexpression of TGF-β3 has been implicated in the pathogenesis of ARPC [21].…”
Section: Discussionmentioning
confidence: 99%
“…ARPC has been described in association with diabetes, chronic renal disease and malignancy and following various inflammatory cutaneous conditions [18, 19]. It corresponds to a transepidermal elimination of necrotic collagen during a peculiar pattern of epidermal regeneration [20]. Overexpression of TGF-β3 has been implicated in the pathogenesis of ARPC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fretzin et al [25]found the extruded collagen histochemically altered but morphologically intact. The ultrastructural integrity was also confirmed by Yanagihara et al [26]. The collagen fibres eliminated through the epidermis showed normal periodicity [27].…”
Section: Discussionmentioning
confidence: 59%
“…Nuestros pacientes cumplen con los criterios clínicos propuestos por Faver, sin embargo, en el diagnóstico histopatológico no se evidencia necrosis de las bandas de colágeno. Esto coincide con reportes que describen que las fibras colágenas no presentan degeneración obvia 8,9 .…”
Section: Discussionunclassified
“…Las enfermedades que más se asocian a la colagenosis perforante reactiva adquirida son la diabetes mellitus y la insuficiencia renal crónica [5][6][7][8][9][10][11][12][13][14][15] , ambas patologías presentes en nuestras pacientes. En un estudio inglés hecho en una población de insuficientes renales crónicos en hemodiálisis, se demostró que 11% presentaba colagenosis perforante reactiva adquirida 15 .…”
Section: Discussionunclassified